Da administração de pessoal a administração estratégica de recursos humanos: evolução natural ou consequência de uma estratégia empresarial: um estudo de caso - Souza, Maria Zélia de Almeida (1996)
The aim of the presente work is to demonstrate, by means of a study carried out within the Lachmann Group, using interviews, questionnaires and workshops, with the Board and employees, that the efficient change in the Group's companies at Human Resources Management - HRM - leveI, was a consequence of Organizational Strategy. The Lachmann Group, who are leaders in the are as of representation and shipping of goods in Latin America, had to face a difficult task with the sudden decease of their Chairrnan: would they be able to cope with the necessary internaI changes plus the environmental pressures created by increasing competition in the sector? Their expectation was positive. But how would they manage to implement such structural changes without losing their characteristics? How could they at the same time go through these changes and also face the growing demand of a market where competition becomes stronger everyday? The answers to all these questions were developed in a process of planned changes, in which the Human Resources area played a key role, carrying out its actions in harrnony with the Corporation's strategic planning and contributing to the fulfillment of their objectives. The result of the survey made in the Lachmann Goup, and supported by the existing literature, allows us to conclude that HRM has an important role in the context of contemporary Business Management. Nevertheless, its efficacy is directly related to the integration between its planning and the company's strategic planning. This association, howeveT, d0es not occur by chance. On the contrary, it is ~he result of Organizational Strategy in which the aspects of human resources are devised withing the company's strategic planning, and provide valuable elements for the Board on decision taking.